2021
DOI: 10.1002/ghg.2137
|View full text |Cite
|
Sign up to set email alerts
|

Role of Co species on Co/KIT‐6 catalyst surface in CO2 hydrogenation

Abstract: Supported Co/KIT‐6 catalyst, which has high specific surface area and well‐developed ordered mesoporous structure, was prepared by wet impregnation method. Its physicochemical properties were characterized by transmission electron microscopy (TEM), Brunner–Emmet–Teller (BET), Low‐angle XRD, in situ X‐ray photoelectron spectroscopy (in situ XPS) and H2‐temperature program reduction (H2‐TPR), and its catalytic properties were investigated by CO2 hydrogenation. The in situ XPS and H2‐TPR results indicated that Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The reported research results confirmed that metal Co species were the mainly active species in CO 2 catalytic hydrogenation, and the composition of Co species could significantly affect CO 2 hydrogenation activity and selectivity [9–11] . The study results on mesoporous Co/SiO 2 catalysts confirmed that the Co species composition, grain size, pore size and pore structure order of the Co/SiO 2 catalysts had a significant effect on the CO 2 hydrogenation activity and selectivity.…”
Section: Introductionsupporting
confidence: 59%
“…The reported research results confirmed that metal Co species were the mainly active species in CO 2 catalytic hydrogenation, and the composition of Co species could significantly affect CO 2 hydrogenation activity and selectivity [9–11] . The study results on mesoporous Co/SiO 2 catalysts confirmed that the Co species composition, grain size, pore size and pore structure order of the Co/SiO 2 catalysts had a significant effect on the CO 2 hydrogenation activity and selectivity.…”
Section: Introductionsupporting
confidence: 59%
“…What is more, it can improve catalytic performances and inhibit catalysts from being sintered by enhancing the properties of surface‐active species. KIT‐6 support is a mesoporous SiO 2 material with I a3d cubic pore structure, which has the advantages of high specific surface area, adjustable pore structure, and high hydrothermal stability, favoring the formation of active centers on the catalyst surface 32–35 . Meanwhile, the abundant pore structure and large surface area of the SiO 2 can promote the stability of active metal phases on the support surface in the process of high temperature calcination or/and reduction.…”
Section: Introductionmentioning
confidence: 99%
“…KIT-6 support is a mesoporous SiO 2 material with I a3d cubic pore structure, which has the advantages of high specific surface area, adjustable pore structure, and high hydrothermal stability, favoring the formation of active centers on the catalyst surface. [32][33][34][35] Meanwhile, the abundant pore structure and large surface area of the SiO 2 can promote the stability of active metal phases on the support surface in the process of high temperature calcination or/and reduction. Thus, metal component sintering and aggregation are prevented, which can improve catalytic performances.…”
mentioning
confidence: 99%
“…For CO 2 hydromethanation catalyst, the research mainly focuses on transition metal Ni and Co catalysts. [2][3][4][5] Metal Ni catalyst has superior deep hydrogenation performances, and the research in CO 2 hydromethanation reaction is more extensive.…”
Section: Introductionmentioning
confidence: 99%